2017
DOI: 10.1089/end.2016.0892
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Tumors and Dual-Band Imaging: A New Concept in Confocal Laser Endomicroscopy

Abstract: Real-time cytodetection was feasible using two fluorophores (FLUO and HAL) and the new system of CVII. This technology was useful to observe cytoplasm, nuclei, and nucleocytoplasmic abnormality, but an improved system is necessary (to overcome the overlapping of fluorescence) to increase the specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Combination of CLE with other endoscopic techniques could be a better choice and may greatly alter current bladder cancer management. Marien et al [28] evaluated the feasibility of using CLE with 2 fluorophores (fluorescein and hexyl aminolevulinate) for bladder cancer diagnosis and found that sensitivity and specificity of this combination can reach 80 and 100%, respectively. However, application of CLE combined with other endoscopic techniques is still in the early stages, and the advantage of various combinations remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of CLE with other endoscopic techniques could be a better choice and may greatly alter current bladder cancer management. Marien et al [28] evaluated the feasibility of using CLE with 2 fluorophores (fluorescein and hexyl aminolevulinate) for bladder cancer diagnosis and found that sensitivity and specificity of this combination can reach 80 and 100%, respectively. However, application of CLE combined with other endoscopic techniques is still in the early stages, and the advantage of various combinations remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Five experiments in four studies reported a sensitivity of more than 90%. Only the study of Marien et al [21] reported sensitivity below 80%. We conducted a pooling effect estimate using Mosses-Litenberg's Bivariate Model and found a pooled sensitivity of 90.2% (0.86, 0.93).…”
Section: Cle Accuracy In Differentiating Malignant and Benign Tumorsmentioning
confidence: 98%
“…Recent meta-analysis showed that combination of OCT with florescence imaging technologies such as BLC could further improve its diagnostic accuracy and avoid unnecessary biopsies (23). The results of ex vivo study of combining OCT and BLC, however, had been disappointing as HAL cannot provide a clear cellular architecture due to due to cytoplasmic localization (24). It has been suggested that combination of RS and molecular targeting nanoparticles, referred to as surface-enhanced RS, can significantly improve sensitivity and specificity for detection of bladder tumors through signal amplification and molecular mapping (4).…”
Section: Combination With Other Enhanced Imaging Techniquesmentioning
confidence: 99%